Offshore Wind Energy Technology 2018
DOI: 10.1002/9781119097808.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Operation and Maintenance Modelling

Abstract: One of the biggest challenges in the development of offshore wind farms is the cost and limited opportunities for maintenance and access. This calls for new solutions when it comes to operation and maintenance (O&M) strategies, condition monitoring and logistics, just to mention some examples. To assess different solutions and to select the best ones, good models for maintenance and logistics decision support are required. This chapter provides an overview of, and a brief introduction to, O&M modelling for off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…For projects, for example, offshore oil and gas production, the construction of «cloud» ports, etc., both land and sea transport are used. Moreover, for offshore oil and gas production projects, various types of sea vessels are involved [2][3][4]: universal -for the transportation of oversized equipment and parts of platforms, tugs -for food, people and equipment of small size.…”
Section: Introductionmentioning
confidence: 99%
“…For projects, for example, offshore oil and gas production, the construction of «cloud» ports, etc., both land and sea transport are used. Moreover, for offshore oil and gas production projects, various types of sea vessels are involved [2][3][4]: universal -for the transportation of oversized equipment and parts of platforms, tugs -for food, people and equipment of small size.…”
Section: Introductionmentioning
confidence: 99%
“…Energy profits from offshore wind farm projects are usually estimated via simulation experiments that mimic wind turbine activity, including turbine failures and associated maintenance activities and logistics, along with physical and weather conditions at sea, yielding economic values as output. Several such simulation tools have been developed, see for instance Hofmann (2011), Welte et al (2018) and Seyr and Muskulus (2019) for overviews.…”
Section: Complex Simulators For Decision Supportmentioning
confidence: 99%
“…The methodologies presented in this paper are motivated by an application involving the operation and maintenance (O&M) of offshore wind farms (Tavner 2012). A survey from Welte et al (2018) indicated that the O&M cost of an offshore farm lies between 12-32% of its total Levelized Cost of Energy (LCOE), and according to a report from the International Renewable Energy Agency, the LCOE for offshore wind turbines is 2.3 times higher than that of onshore wind turbines (IRENA 2018). For offshore wind power to be competitive with other sources of renewable energy, the costs related to O&M must hence be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The second category of research (for example, [13,14) addresses the maintenance of field development projects. The focus of such studies is either a service schedule [14] or the optimization of service processes in terms of routes [15]. In addition, in some studies, transportation is considered as a project, that is, a design-oriented approach to cargo delivery is used [16].…”
Section: Research Of Existing Solution Of the Problemmentioning
confidence: 99%